Fully biodegradable electrochromic display for disposable patch - Se-Hun Kang; Ju-Yong Lee; Joo-Hyeon Park; Sung-Geun Choi; Sang-Ho Oh; Young-Chang Joo; Seung-Kyun Kang (npj Flexible Electronics)
Abstract Flexible and biodegradable electronics have emerged as a promising solution for escalating electronic waste issue caused by the rapid development of skin patch electronics. Fully biodegradable displays are essential for visualizing biological/physical/chemical/electrochemical signals measured by a wide range of skin patch electronics. Here we propose fully biodegradable electrochromic display providing low operating voltage and low power consumption. The biodegradable transparent conductive electrode was fabricated by transferring free-standing tungsten nanomesh onto poly lactic-co-glycolic acid substrate using electrospinning templating, minimizing damage to the substrate. Electrochromic layer was tungsten oxide which is biodegradable, and a ferrocyanide/ferricyanide redox agent was utilized as a counter electrode reaction to enhance operational stability in an aqueous electrolyte by reducing operating voltage and side reactions. This display successfully visualized diverse signals from various biodegradable electronics such as UV sensors and electrochemical transistors, and finally underwent eco-friendly degradation in phosphate-buffered saline or soil under mild conditions.